Importing sobrie'tea': Understanding the tea trade during the Industrial Revolution - Kabeer Bora (The University of Utah, Department of Economics, 2023)
Economic historian Robert Allen observed that during the Industrial Revolution, the British working class experienced a period of stagnant real wages. This has led many historians to investigate changes in the diet of the working class during that time. While there has been a focus on the entire food basket, this paper concentrates on the consumption of tea, which was entirely imported. I seek to explore why demand for tea increased during the Industrial Revolution by examining the effect of working hours on tea imports between 1760 and 1834. I aim to identify the determinants of tea demand and while underlining the crucial role that increasing working hours played in surplus extraction. The Industrial Revolution was characterized by long working hours, and the declining consumption per capita of so-called luxury items, such as tea, was actually due to their use as stimulants. To examine the relationship between working hours and tea imports, I employ a Dynamic OLS (DOLS) methodology, which demonstrates that tea imports responded positively to increasing working hours. This finding is corroborated by another method, the Fully Modified OLS (FM-OLS). I also propose new methods for calculating hours worked and tea imports in the process.
Keywords: N33; J22; I15; N73; F14; 330; Tea; Working hours; Time Series; Trade History; Industrial Revolution